Sperm Quality of Various Breeds and Ages of Bull in the Singosari Artificial Insemination Center - Sulaeman, La Ode Syawal; Priyanto, Rudy; Supriatna, Iman; Suharto, Kresno; Setiyono, Achmad (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
This study aimed to evaluate the effect of breeds and bulls ages on semen volume, sperm concentration, total number sperm, progressive motility, and sperm abnormalities of semen bull. The data used in the form of semen quality data from the Singosari National Artificial Insemination Center from the period 2021 to 2022. The bulls used each returned 4 bali, simmental and limousin. With age categories 3-4 years, 5-6 years, 7-8 years and 9-10 years. The research design used was a completely randomized factorial design. Data sperm quality were analyzed by general linear model method followed by LS mean. Sperm quality studied showed an interaction (P<0.05) between breed and age on the volume semen, sperm concenration, total number sperm,  progressive motility and sperm abnormalities. Bali cattle have a longer semen production period than simmental and limousine cattle. Bali cattle can be used until the age of 9-10 years, while simmental and limousine cattle can only be used until the age of 7-8 years.